Bond Yields and the Federal Reserve - Piazzesi, Monika (Journal of Political Economy, 2005)
Bond yields respond to policy decisions by the Federal Reserve and vice versa. To learn about these responses, I model a high‐frequency policy rule based on yield curve information and an arbitrage‐free bond market. In continuous time, the Fed's target is a pure jump process. Jump intensities depend on the state of the economy and the meeting calendar of the Federal Open Market Committee. The model has closed‐form solutions for yields as functions of a few state variables. Introducing monetary policy helps to match the whole yield curve, because the target is an observable state variable that pins down its short end and introduces important seasonalities around FOMC meetings. The volatility of yields is "snake shaped," which the model explains with policy inertia. The policy rule crucially depends on the two‐year yield and describes Fed policy better than Taylor rules.